Advances in Capacitor Health Monitoring Techniques for Power Converters: A Review - Ramees, M. K. P. Muhammed; Ahmad, Md. Waseem (IEEE access, 2023)
Capacitors play a critical role in power electronic systems, and their health and performance directly impact system reliability and efficiency. This article provides an overview of advanced techniques developed for capacitor monitoring, focusing on diagnosing, estimating, and predicting capacitor health in various power electronic converters. The condition monitoring techniques are categorized based on the type of converter, and a comprehensive review and comparison of various methods are provided within each category. The article covers various techniques, including impedance spectroscopy, frequency response analysis, harmonic analysis, wavelet analysis, short-time Fourier transform, and algorithm-based predictive models. These techniques enable early detection of capacitor faults, accurate estimation of capacitance and equivalent series resistance (ESR), and prediction of the remaining useful life of capacitors. By implementing these advanced monitoring techniques, engineers and researchers can enhance system reliability, prevent unexpected failures, and optimize maintenance and replacement strategies for capacitors in power electronic systems.